Analisis Neraca Pendidikan Tingkat SMA Kabupaten Indragiri Hilir - Oki Rasdana; Elvrin Septyanti; Silvia Permatasari; Zulhafizh Zulhafizh; Tria Putri Mustika (Departement of Mathematics Education, 2023)
This study aims to look at the balance of education at the senior high school level in Indragiri Hilir Regency with all the limitations as a district that does not have natural resources like other districts in Riau. Moreover, at the high school level is the average standard of the world of work today as the beginning of a career to become an adult human being. The research method is descriptive qualitative with data collection techniques from literature studies which are analyzed using spiral data analysis techniques through purposive sampling. The results are 1) a sufficiently qualified budget 2) IPM which increased by 0.74% from the previous year 3) APK of 50.29% and APM of 69.67% still do not meet government standards 4) many teachers are fresh graduates, the status of civil servant teachers is still small to very many teachers who are not certified 5) more than 50% need minor repairs 6) 1/4 school need to increase accreditation. Based on these results, it can be concluded that education in Indragiri Hilir Regency at the high school level is still quite good.